Olivine in the Udachnaya-East Kimberlite (Yakutia, Russia): Types, Compositions and Origins - Kamenetsky, Vadim S.; Kamenetsky, Maya B.; Sobolev, Alexander V.; Golovin, Alexander V.; Demouchy, Sylvie; Faure, Kevin; Sharygin, Victor V.; Kuzmin, Dmitry V. (Journal of Petrology, 2008)
Olivine is the principal mineral of kimberlite magmas, and is the main contributor to the ultramafic composition of kimberlite rocks. Olivine is partly or completely altered in common kimberlites, and thus unavailable for studies of the origin and evolution of kimberlite magmas. The masking effects of alteration, common in kimberlites worldwide, are overcome in this study of the exceptionally fresh diamondiferous kimberlites of the Udachnaya-East pipe from the Daldyn–Alakit province, Yakutia, northern Siberia. These serpentine-free kimberlites contain large amounts of olivine (∼50 vol.%) in a chloride–carbonate groundmass. Olivine is represented by two populations (olivine-I and groundmass olivine-II) differing in morphology, colour and grain size, and trapped mineral and melt inclusions. The large fragmental olivine-I is compositionally variable in terms of major (Fo 85–94 ) and trace element concentrations, including H 2 O content (10–136 ppm). Multiple sources of olivine-I, such as convecting and lithospheric mantle, are suggested. The groundmass olivine-II is recognized by smaller grain sizes and perfect crystallographic shapes that indicate crystallization during magma ascent and emplacement. However, a simple crystallization history for olivine-II is complicated by complex zoning in terms of Fo values and trace element contents. The cores of olivine-II are compositionally similar to olivine-I, which suggests a genetic link between these two types of olivine. Olivine-I and olivine-II have oxygen isotope values (+ 5·6 ± 0·1‰ VSMOW, 1 SD) that are indistinguishable from one another, but higher than values (+ 5·18 ± 0·28‰) in ‘typical’ mantle olivine. These elevated values probably reflect equilibrium with the Udachnaya carbonate melt at low temperatures and 18O-enriched mantle source. The volumetrically significant rims of olivine-II have constant Fo values (89·0 ± 0·2 mol%), but variable trace element compositions. The uniform Fo compositions of the rims imply an absence of fractionation of the melt's ...